Comparison of HemoFoam® and Conventional Gauze Dressing on Hemostasis of Vascular Access Site in Hemodialysis Patients: - zarepur, rouhollah; Bizari, Davood; Khoshmohabat, Hadi; Salahshour Kordestani, Soheila (Galen Medical Journal, 2019)
Background: Dialysis access puncture wound bleeding after needle extraction at the end of each hemodialysis session is a very important problem. This study evaluated the effect of HemoFoam® compared to conventional gauze dressing on hemostasis of dialysis access puncture wound bleeding in hemodialysis patients. Materials and Methods: This one-group, before-after, clinical-trial was conducted on 60 hemodialysis patients selected by convenience sampling who underwent hemodialysis through arteriovenous fistula in Shahid Rahnemoon Hospital, Yazd, Iran in 2017. After reviewing the eligibility criteria, the study was performed in two separate sessions. In the first session, only HemoFoam® was used while in the second session; the only conventional dressing was used. Time of hemostasis in each puncture wound was evaluated. Data were analyzed by SPSS 22 (IBM SPSS Statistics for Windows, Armonk, NY: IBM Corp, United States) using paired T-test and Chi-square tests. Results: The mean age of the patients was 55.20±14.25 years. Hemostasis was achieved in 76.6% of cases at the arterial access site in the first two minutes in the HemoFoam® group. The mean homeostasis time in the HemoFoam® group was 2.86±1.87 min at the venous access site and 3.15±1.97 min at the arterial access site (P<0.001). The mean homeostasis time in the conventional dressing group was 10.54±6.65 min at venous access site and 12.74±9.28 min at the arterial access site, which was significantly different between the two groups (P<0.001). Conclusion: HemoFoam® is effective in reducing the time of homeostasis in the vascular access site of hemodialysis patients. Therefore, its use in hemodialysis wards is recommended for hemostasis in the dialysis access puncture wound bleeding. [GMJ.2019;8:e1395]